Management : - Kinicki, Angelo (McGraw Hill, 2008)
Our primary goal is simple to state but hard to execute: to make learning principles of management as easy, efficient, and effective as possible. Accordingly, the book intergrates writing , illustration, design, and manazine-like layout in a program of learning that appeals to the visual sensibilities and respects the time constraints and different learning styles of today's student.